Barriers to implementation of "Academia da saúde program" in Santa Catarina (Journal of Physical Education (Maringá), 2019)
The Ministry of Health established the Academia da Saúde Program (PAS) with the objective of contributing to the promotion of health, the implementation of policies for the conduct of physical activities, physical activity and leisure and the reduction of healthy lifestyles. The objective of this study was to identify managers of physical activity programs on the barriers to the operation of the PAS poles in Santa Catarina (SC). A cross-sectional study was carried out with 26 managers (61.5% women) of physical activity programs in Santa Catarina. As compensation payments were withdrawn from the base for updating health statistics. Descriptive statistics (mean, standard avoidance, absolute and relative frequency) were made for data analysis. The results triggered a lack of human resources, lack of leadership, lack of materials, facilities, equipment and a lack of standardized instruments to carry out an evaluation of actions. It was concluded that organizational, infrastructure and human resources barriers are present in the day-to-day actions of PAS in SC.